The changing demographics and severity in hospitalized patients across COVID-19 variants: A national cohort study - Priyanka Parajuli; Lara A.C. Phipps; Roy Sabo; Rasha Alsaadawi; Amanda Robinson; Evan French; Richard K. Sterling; N3C. consortium (Journal of Clinical and Translational Science)
Abstract